Organizational Sentencing Guidelines: The Cart Before the Horse - Pamela H. Bucy (Washington University Law Quarterly, 1993)
Part I of this Article provides a brief overview of the Guidelines and discusses how they define and measure corporate culpability. Part II describes and critiques the current standards for assessing corporate criminal liability. Part III proposes a new standard of corporate criminal liability that builds upon premises inherent in the Guidelines. Finally, Part IV addresses the question of whether a need remains for a new standard of corporate criminal liability in light of the federal organizational Sentencing Guidelines.
Keywords: Criminal liability of juristic persons; Sentencing guidelines (Criminal procedure)